Paediatric autoimmune hepatitis with thalassemia trait: a case report - Ali, Mohammad Amir; Behera, Braja Kishore (International Journal of Contemporary Pediatrics, 2026)
Autoimmune hepatitis (AIH) is a chronic inflammatory liver condition characterized by elevated serum aminotransaminase levels, the presence of liver-associated autoantibodies, and/or hypergammaglobulinemia. Three conditions with likely autoimmune origins include AIH, autoimmune sclerosing cholangitis, and de novo AIH following liver transplantation. AIH is classified into two types based on antibody presence: Type 1 and Type 2. Systemic disorders such as hemoglobinopathies, cystic fibrosis, and histiocytic disorders have been associated with liver dysfunction. Early diagnosis requires a high level of suspicion. Paediatricians should consider AIH in patients presenting with jaundice after excluding common causes. The diagnosis is made through a combination of biochemical, immunological, and histological findings, while ruling out other liver diseases with similar serological and histological profiles. We present the case of an 8-year-old female with non-resolving jaundice, diagnosed with AIH alongside thalassemia trait.